Epidemiology, Antibiotic Susceptibility and Serotype Distribution of Streptococcus pneumoniae Associated with Invasive Pneumococcal Disease in British Columbia - A Call to Strengthen Public Health Pneumococcal Immunization Programs. (1st October 2003) - Bigham, Mark; Patrick, David M; Bryce, Elizabeth; Champagne, Sylvie; Shaw, Carol; Wu, Wrency; Ng, Helen; Roscoe, Diane; Roy, Jacques; Isaac-Renton, Judy
Abstract : BACKGROUND: This study examined the epidemiology, antibiotic susceptibility and serotype distribution of Streptococcus pneumoniae associated with invasive pneumococcal disease (IPD) in British Columbia. METHODS: Six hospitals and one private laboratory network participated in a prospective, sentinel laboratory based surveillance study of IPD, between October 1999 and October 2000. At each site, S pneumoniae isolates were collected and epidemiological data were gathered using a structured questionnaire, for all cases of IPD meeting the study case definition. Isolates were serotyped and tested for antimicrobial susceptibility. Bivariate associations were analyzed and multivariate logistic regression was used to identify independent risk factors associated with hospitalization or death. RESULTS: One hundred three reports and isolates were collected. Seventy-nine per cent of cases were community-acquired, 64% required hospitalization and 5% died. Cases with one or more assessed risk factor for IPD and of female sex were independent variables associated with hospitalization or death. One-third of isolates had reduced penicillin susceptibility and 96% of these represented serotypes contained in the 23-valent pneumococcal polysaccharide vaccine (PPV-23). Overall, 89% of serotypes identified are included in the PPV-23 vaccine and 88% of isolates from children under five years of age are found in the 7-valent pneumococcal conjugate vaccine (PCV-7). Forty-one per cent of cases qualified for publicly funded pneumococcal vaccine and 34% of eligible persons were vaccinated. CONCLUSIONS: Overall, pneumococcal serotypes associated with IPD in this study closely matched serotypes included in PPV-23 products currently licensed in Canada. Most serotypes associated with IPD in children under five years of age are included in a recently licenced PCV-7. One third of isolates demonstrated reduced penicillin susceptibility, most involving serotypes included in PPV-23. Effective delivery of current public health immunization programs using PPV-23 and extending protection to infants and young children using the PCV-7 will prevent many cases of IPD.